Intersecting Strategies: A Comparative Analysis of the BRI, C5+1 and Eurasian Economic Union in Central Asia - Iqra Javed; Syed Nouman Ali Shah, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
This paper explains that although the Belt and Road Initiative (BRI), the Eurasian Economic Union (EAEU) and C5+1 frameworks are frequently portrayed as rival geopolitical projects in the region, in reality, all of them reproduce asymmetric power relations that constrain the strategic autonomy of regional state. This study employs a comparative qualitative research design and relies both primary and secondary sources to examine the BRI, EAEU and the C5+1 framework as rival but overlapping systems of external impact on Central Asia. By applying a comparative institutional and geoeconomic approach, the paper reveals that China through its infrastructure driven financing, Russia through its regulatory assimilation and the United States through its governance-based diplomacy represents distinct but complementary mechanisms of external influence. Although the governments of Central Asia use multi-vector diplomacy to multiply partners and maximize the benefits, the given strategy is mostly used within the frames of structural constraints imposed by external forces. The results indicate that multi-vectorism functions less as a route to actual regional empowerment and more as an adaptive survival strategy within a disintegrated Eurasian order.